If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.5(8 + x) = -16 (8 * 0.5 + x * 0.5) = -16 (4 + 0.5x) = -16 Solving 4 + 0.5x = -16 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 0.5x = -16 + -4 Combine like terms: 4 + -4 = 0 0 + 0.5x = -16 + -4 0.5x = -16 + -4 Combine like terms: -16 + -4 = -20 0.5x = -20 Divide each side by '0.5'. x = -40 Simplifying x = -40
| 7(6-5n)+2(3-4n)=45 | | 8.14x+13.02=5.16x+33.88 | | 3(2t-6)=3t | | e+.5=9 | | (3x*3x+7)+(3x*3x+9)= | | 5-0.50(b-6)=4 | | -x/8=x+2/6 | | 8.14+13.02=5.16x+33.88 | | (2/3)(3x+27)=x+5 | | -3y^2-26y-45=0 | | z+3.2=57 | | p-3=-2 | | 116=p*400 | | 5x=5x+40 | | 5x=4x+312 | | 2x=5x+40 | | -9x+6=-10x-6 | | 9x+50=3x(2)+10 | | 104=4(4-6n) | | 500+22p=1204 | | 2+2x=2x-46 | | 30x-10=x+4x-5+2x+7 | | 6-2y=1+y | | -(a-6)=-(2a+1)-2 | | 2t+3(1-4t)= | | 5(2x+11)-3*5= | | -3u^2-26u-45=0 | | 3d-7=32 | | 2x+14y=24 | | 14x*14x-9x*9x= | | -6=-b^2+b | | x^2+2x+y-1=0 |